2023
DOI: 10.3389/fpsyt.2023.1259481
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive transcranial magnetic stimulation for apathy in patients with neurodegenerative conditions, cognitive impairment, stroke, and traumatic brain injury: a systematic review

Adrian I. Espiritu,
Takatoshi Hara,
Joy Kirsten Tolledo
et al.

Abstract: BackgroundWe aimed to determine the effects and tolerability of repetitive transcranial magnetic stimulation (rTMS) on apathy in patients with neurodegenerative conditions, mild cognitive impairment (MCI), stroke, and traumatic brain injury (TBI) via systematic review.MethodsWe conducted a systematic search in major electronic health databases, including PubMed, Scopus, and PsycINFO, covering the period from inception to June 2023. Comparative clinical trials and cohort studies, and studies with before-after d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 104 publications
0
1
0
Order By: Relevance
“…A recent meta-analysis of 12 randomised control trials of repetitive TMS for treating both motor and non-motor symptoms in PD demonstrated high-frequency rTMS applied to the dlPFC improved depressive symptoms compared to a placebo, but it did not specifically look at apathy as an outcome [103]. Overall, there is a growing body of literature supporting the use of TMS as an adjunct therapy for apathy for patients with neurodegenerative conditions, but the evidence regarding PD-related apathy is not as strong as it is for other conditions like Alzheimer's disease, and further large trials are needed [104].…”
Section: Transcranial Magnetic Stimulationmentioning
confidence: 99%
“…A recent meta-analysis of 12 randomised control trials of repetitive TMS for treating both motor and non-motor symptoms in PD demonstrated high-frequency rTMS applied to the dlPFC improved depressive symptoms compared to a placebo, but it did not specifically look at apathy as an outcome [103]. Overall, there is a growing body of literature supporting the use of TMS as an adjunct therapy for apathy for patients with neurodegenerative conditions, but the evidence regarding PD-related apathy is not as strong as it is for other conditions like Alzheimer's disease, and further large trials are needed [104].…”
Section: Transcranial Magnetic Stimulationmentioning
confidence: 99%